Penerapan Model Pembelajaran IPS Inside Outside Circle Berbantuan Power Point Interaktif - Wovie Azizah; Lucy Arsi Purwasih; Aren Frima (Journal of Elementary School (JOES), 2023)
This study aims to determine the social studies learning outcomes of fifth grade students at SD Negeri 72 Lubuklinggau after the Inside Outside Circle Power Point Interaktif learning model has been applied significantly. This research method uses experimental research methods with pre-test and post-test experimental designs. Sampling was taken from the total population considering that there was only one class of the population, the population was the sample in this study, namely fifth grade students, totaling 24 students. The instrument used by the researcher was in the form of essay questions which totaled 8 questions. Data collection is taken by test technique. Data analyzed using the "Z” test formula. Based on the results of the hypothesis testing then Z_count was consulted with Z_table on the "Z" distribution list with a significant level of α = 0.05 so that Z_count = 9,94 and Z_table = 1.64, then Z_count = 9,94 ≥ Z_table = 1.64 with this, H_o is rejected and H_a is accepted. So it can be concluded that the Inside Outside Circle Power Point Interaktif learning model can complete social studies learning outcomes for fifth grade students at SD Negeri 72 Lubuklinggau. Keywords: Inside Outside Circle, Power Point Interaktif, IPS Learning Outcomes